Strain Hardening Cement Composites: Structural Design and Performance State-of-the-Art Report of the RILEM Technical Committee 208-HFC, SC3 - Toshiyuki, Kanakubo. (RILEM State-of-the-Art Reports, 2013)
Strain Hardening Cement Composites, SHCC hereafter, demonstrate excellent mechanical behavior showing tensile strain hardening and multiple fine cracks. This strain hardening behavior improves the durability of concrete structures employing SHCC and the multiple fine cracks enhance structural performance. Reliable tensile performance of SHCC enables us to design structures explicitly accounting for SHCC’s tensile properties. Reinforced SHCC elements (R/SHCC) indicate large energy absorbing performance under large seismic excitation. Against various types of loads, R/SHCC elements can be designed by superimposing re-bar performance and SHCC’s tensile performance.  This report focuses on flexural design, shear design, FE modeling and anti-seismic design of R/SHCC elements as well as application examples.  Establishing design methods for new materials usually leads to exploring application areas and this trend should be demonstrated by collecting actual application examples of SHCC in structures.